Ketika Hakim Ikut Berkampanye: Intervensi Yudikatif dalam Pilpres 2024 - Ayu Safitri Azah Fadhila; Dwi Windyastuti Budi Hendrarti; Nuke Faridha Wardhani (Pusat Riset dan Inovasi Nasional, 2025)
This article discusses the judicial intervention that occurred in the 2024 Presidential and Vice Presidential Election in Indonesia, focusing on the Constitutional Court Decision No.90/PUU - XXI/2023. The study aims to analyze the impact of this decision on the political process, judicial ethics, and the quality of democracy in Indonesia. The method used is a qualitative approach with literature study. The findings indicate that judicial intervention can undermine the rule of law and public trust in the judiciary. There are also indications of a conflict of interest involving the Chief Justice of the Constitutional Court, which could violate democratic principles. Reforms in the oversight and selection of judges are proposed as steps to uphold constitutional integrity and strengthen democracy in Indonesia.